The translation and validation of the Organ Transplant Symptom and Well-Being Instrument in China. - Ying Shi; Zhang Dan; Zijun Tao; Qi Miao; Tiantian Chang; Xu Zhang; Xiaoyu Jiang; Xiaofei Li (Public Library of Science (PLoS), 2022)
To translate the Organ Transplant Symptom and Well-Being instrument (OTSWI) into Chinese and test the reliability and validity of the Chinese version. A total of 259 patients with organ transplants were recruited from The First Affiliated Hospital of China Medical University in Shenyang, from November 2020 to January 2021. Construct validity was evaluated using exploratory factor analysis (EFA) and reliability were assessed using test-retest reliability and internal consistency. The Cronbach's α of the Chinese version of the Organ Transplant Symptom and Well-being instrument was 0.93. EFA demonstrated that 80.785% of the total variance was explained by a seven-factor solution. The criterion validity of the SF-36 was -0.460 (p < .01), while the test-retest reliability was 0.710. The Chinese version of the OTSWI questionnaire is a valid and reliable instrument for assessing the quality of life of organ transplant patients for symptoms and well-being in China.